2021
DOI: 10.1055/a-1328-2847
|View full text |Cite
|
Sign up to set email alerts
|

Two-Year Follow-Up: Therapeutic Success with Respect to Axial Length of Stand-Alone Xen45 Gel Stent Implantation and Combined Procedures

Abstract: Background Up to now, no data have been available on the therapeutic success rate of Xen45 gel stent with respect to axial length (AL). The present study aimed to investigate a potential influence of AL on therapeutic success in stand-alone Xen45 gel stent implantation or combination with cataract surgery in open-angle glaucoma patients (OAG) with a follow-up of 2 years. Materials and Methods In this retrospective observational study, 98 eyes of 87 glaucoma patients of the Department of Ophthalmology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 23 publications
(34 reference statements)
0
9
0
Order By: Relevance
“…Follow-up to 24 months was reported in 17 studies (n = 1154 eyes). 12,21,22,[32][33][34]36,37,[49][50][51][52][56][57][58]60,65 The weighted mean preoperative IOP was 18.4 mm Hg on 2.5 medications and the weighted mean postoperative IOP was 14.2 mm Hg on 0.9 medications. Follow-up to 36 months was reported in 6 studies (n = 294 eyes).…”
Section: Efficacy Outcomesmentioning
confidence: 96%
See 4 more Smart Citations
“…Follow-up to 24 months was reported in 17 studies (n = 1154 eyes). 12,21,22,[32][33][34]36,37,[49][50][51][52][56][57][58]60,65 The weighted mean preoperative IOP was 18.4 mm Hg on 2.5 medications and the weighted mean postoperative IOP was 14.2 mm Hg on 0.9 medications. Follow-up to 36 months was reported in 6 studies (n = 294 eyes).…”
Section: Efficacy Outcomesmentioning
confidence: 96%
“…The weighted mean Forty-five studies (n = 3122 total eyes) reported 12-month outcomes with complete pre-and postoperative IOP and medication use. 4,5,[10][11][12]15,19,20,25,[27][28][29][30][31][32][33][35][36][37][38][39][40][42][43][44][45][46][47][48][51][52][53]55,[57][58][59][60][62][63][64][65][66][67][68] In these studies, the median number of eyes followed was 52 (range, 12-242) and median age was 72.2 years (range, 53.4-80.9). The weighted mean preoperative IOP was 22.2 mm Hg on 2.5 glaucoma medications, and the weighted mean postoperative IOP was 14.2 mm Hg on 0.7 glaucoma medications.…”
Section: Efficacy Outcomesmentioning
confidence: 97%
See 3 more Smart Citations